2023
DOI: 10.1126/scitranslmed.abj3138
|View full text |Cite
|
Sign up to set email alerts
|

Proregenerative extracellular matrix hydrogel mitigates pathological alterations of pelvic skeletal muscles after birth injury

Abstract: Pelvic floor disorders, including pelvic organ prolapse and urinary and fecal incontinence, affect millions of women globally and represent a major public health concern. Pelvic floor muscle (PFM) dysfunction has been identified as one of the leading risk factors for the development of these morbid conditions. Childbirth, specifically vaginal delivery, has been recognized as the most important potentially modifiable risk factor for PFM injury; however, the precise mechanisms of PFM dysfunction after parturitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…This relationship is in line with several studies [9, 47] showing interruptions to FAP signaling and extracellular protein deposition result in MuSC dysfunction. [4850] While more studies are needed to further elucidate how FAPs shape and remodel the ECM and MuSCs correspondingly change state and respond, engineered platforms [51] may offer a unique system [52] to evaluate this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is in line with several studies [9, 47] showing interruptions to FAP signaling and extracellular protein deposition result in MuSC dysfunction. [4850] While more studies are needed to further elucidate how FAPs shape and remodel the ECM and MuSCs correspondingly change state and respond, engineered platforms [51] may offer a unique system [52] to evaluate this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…56 Upon injection or incubation at body temperature, the digested liquid ECM self-assembles into a porous and nanofibrous scaffold that likewise supports cell infiltration and promotes a proremodeling immune response. 57 Duran et al 58 studied the role of a porcine-derived skeletal muscle ECM hydrogel in the PFMs of a rat SBI model. They found that the injection of the ECM hydrogel increased the fiber area compared with untreated animals and animals injected with saline when injected either coincidentally with the SBI as well as 4 weeks later (simulating injection at the postpartum visit), 58 suggesting that this strategy could be used to prevent or treat postpartum PFM degeneration.…”
Section: Acellular Biomaterials Scaffoldsmentioning
confidence: 99%
“…57 Duran et al 58 studied the role of a porcine-derived skeletal muscle ECM hydrogel in the PFMs of a rat SBI model. They found that the injection of the ECM hydrogel increased the fiber area compared with untreated animals and animals injected with saline when injected either coincidentally with the SBI as well as 4 weeks later (simulating injection at the postpartum visit), 58 suggesting that this strategy could be used to prevent or treat postpartum PFM degeneration. In general, these bioinductive scaffolds show promise in improving the way that we approach PFDs, and provide options for managing complications associated with permanent synthetic materials.…”
Section: Acellular Biomaterials Scaffoldsmentioning
confidence: 99%
“…Hydrogel injection was associated with myogenesis, reduced atrophy, and decreased expression of profibrotic genes. 46 Hydrogels can provide a conducive microenvironment for tissue repair that harnesses the endogenous properties of extracellular matrix.…”
Section: Synthetic Scaffoldsmentioning
confidence: 99%